God(bots) and Authority: Trust and Faith in the Age of AI - Davis, Benjamin Clay; Cotter, Kelley; Kanthawala, Shaheen; De, Ankolika; Liu, Yupo; Ritchart, Amy; McAtee, Haylee (AoIR Selected Papers of Internet Research, 2026)
In this paper we systematically survey emergent religious and spiritual (R/S) AI chatbot applications and outline our plans to conduct application walkthroughs to collect and analyze developer discourses. Our research asks: 1) How is authority, through trust and/or faith, discursively constructed around R/S chatbots? 2) How do developers synthesize Silicon Valley worldviews with existent R/S beliefs within the discursive construction of their applications? We sought to answer these questions by first conducting a systematic survey of existing R/S AI integrated applications on DuckDuckGo, iOS App Store, and Google Play Store. Through this we found that applications were framed in three primary ways by their creators as assistants, tools to be used, avatars, mentors embodying a particular R/S figure, and/or angels, beings with access to higher knowledge. These framings will inevitably shape how these tools are received and interpreted by their users, influencing the perceived R/S authority of an AI chatbot. Future work will conduct walkthroughs of a selection of applications from each data collection site. This will generate richer data detailing the material and discursive elements of R/S chatbots to be analyzed through discourse analysis. Our work will highlight how developers frame their creations and explore the potential complications that emerge when blending R/S belief and technological practice. We contribute to existing work on the intersection of R/S and technology and push the field forward by examining the under-explored and emergent development of AI integration into R/S practices.